Estimation of Gypsum- Calcite Percentages Using a Fourier Transform Infrared Spectrophotometer (FTIR), in Alexandria Gypsiferous Soil -Iraq - Al Dabbas, Moutaz; Y. Eisa, Mohammed; H. Kadhim, Weam (Iraqi Journal of Science, 2025)
In this study the Fourier Transform Infrared Spectrophotometry (FTIR) provides a quick, efficient and relatively inexpensive method for identifying and quantifying gypsum concentrations in the samples taken from different sites from different localities from Alexandria district southwest Baghdad. A comprehensive spectroscopic study of gypsum-calcite system was reported to give good results for the first time by using IR for analytical grades of gypsum (CaSO4.2H2O) and calcite (CaCO3) pure crystals. The spectral results were used to create a calibration curve relates the two minerals concentrations to the intensity (peaks) of FTIR absorbance and applies this calibration to specify gypsum and calcite concentrations in Iraqi gypsiferous soil samples, which were collected from different quarries at Alexandria district-Babylon Governorate , southwest of Baghdad city. The peaks were assigned to the fundamental vibrational modes of (SO4)-2 in gypsum and (CO3)-2 in calcite. Thus FTIR appears to provide fast and reliable method for identifying gypsum and calcite concentrations in the gypsiferous soils or any sediments or rocks that have different concentrations of these two minerals.